Beyond Hype and Hardware: The Structural Determinants of EdTech Sustainability in Ethiopia's Quest for SDG 4 - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
Ethiopia, Africa's second most populous nation, confronts a profound educational paradox: a youthful demographic dividend—with over 70% of the population under 30, coexists with a failing education system characterised by a 8.4% university admission rate, 42% graduate unemployment, and over 9 million children out of school. Educational technology (EdTech) has been heralded as a transformative solution, yet sustainability remains elusive. This paper critically examines the structural determinants shaping EdTech sustainability in Ethiopia, moving beyond techno-solutionist narratives to interrogate the interconnected infrastructural, human, financial, and geopolitical factors that perpetuate a self-reinforcing vicious cycle of unsustainability. Employing a Critical Interpretive Synthesis (CIS) combined with a single-embedded case study design, the study synthesises evidence from policy documents, startup ecosystem data, and scholarly literature. The findings reveal that infrastructural failure, characterised by unreliable electricity (44% rural access), limited connectivity (9% rural internet penetration), and prohibitive data costs diminishes teacher morale and agency, reducing technology utilisation and perceived impact. This dissuades investors, reinforcing governmental reluctance to scale digital contracts and perpetuating infrastructural neglect. The paper introduces the 3-P Alignment Model (People, Partnerships, Policy) as an analytical framework for sustainable EdTech deployment. Policy recommendations include prioritizing universal electrification and subsidized bandwidth over hardware procurement, shifting donor funding from short-term pilots to patient capital (5-10 year horizons), and centring foundational literacy through low-tech, high-touch approaches. The paper concludes that systemic integration, not piecemeal digitization, constitutes the only sustainable pathway to leveraging technology for educational development in Ethiopia and analogous fragile states.